Di- and tetranuclear gadolinium (III) complexes of 2-hydroxypropane-1,2,3-tricarboxylic acid and 1,2,2-trimethylcyclopentane-1,3-dicarboxylic acid : identification and characterization - Riri, Mohammed; Hadhoudi, Farid; Hor, Mustapha; Ezzemouri, Samir; Eljaddi, Tarik; Benajjar, Adelkhalek; Hlaibi, Miloudi (International Journal of Advanced Chemistry, 2017)
Our studying involved, Identification and characterization of two novel gadolinium complexes with 2-hydroxypropane-1,2,3-tricarboxylic acid (citric acid) noted H3L and 1,2,2-trimethylcyclopentane-1, 3-dicarboxylic acid (camphoric acid) noted H2L in aqueous solution and in pH range 5,5–7,5. These acids containing the donor atoms (oxygen of OH and COOH), the formatted complexes are colorless and have no absorption band UV–visible. So, to determine the composition and stabilities of these complexes in solution, we have used an analytical technique called «Indirect Photometry Detection (IPD) » have identified multi-nuclear and multi-dentate complexes studied in this work. Giving for these colorless complexes with a mole ratio (M:L): (4:2) for Gd (III)–Citric acid and (2:2) Gd (III)–Camphoric acid. In addition, we have shown that the compositions and stabilities constant of these complexes are depended on the acidity of the medium.